Pengaruh Kepemimpinan Organisasi Dan Komitmen Organisasi Terhadap Kepercayaan Organisasi Dan Kinerja Karyawan - Suripto, Teguh (Jurnal Bisnis Teori & Implementasi)
This study aims to examine the effect of partially between leadership and organizational commitment to organizational trust and employee performance. By using regression analysis, there are two models that will do the testing, the model will first examine the effect of partially between organizational leadership and organizational commitment as an independent variable of organizational trust as the dependent variable. The second model will test the partial between organizational leadership, commitment and trust organization of employee performance.Â